A facile approach to C-functionalized β-ketoimine compounds via terminal alkylation of a tetralithiated intermediate. Issue 21 (16th May 2022) - Zhou, Shuai; Xu, Xiaojuan; Zhu, Xu; Zheng, Yu; Chen, Sufang; Xue, Mingqiang
Abstract : An innovative way to tune β-ketoiminate preligands was provided and the process of alkylation was clarified. Abstract : A series of C -functionalized β-ketoimine compounds at the terminal methyl groups of the β-ketoimine precursor L ph H2 (L ph = C6 H4 [NC(Me)CHC(Me)O]2 ) were prepared. This convenient transformation was realized via straightforward double alkylation on the terminal Cα of a novel bis-dianionic β-ketoiminate lithium complex [L ph′ Li4 (THF)4 ]2 (L ph′ = C6 H4 [NC(Me)CHC(O)CH2 ]2 ) followed by hydrolysis.